2018
DOI: 10.1111/nep.13537
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of chronic kidney disease in Australian general practice: National Prescribing Service MedicineWise MedicineInsight dataset

Abstract: Aim To describe sociodemographic characteristics and comorbidities of a large cohort of Australian general practice‐based patients identified as having chronic kidney disease (CKD), using data from National Prescribing Service (NPS) MedicineWise's MedicineInsight dataset, and compare this dataset to the 2011–2012 Australian Health Survey's (AHS) CKD prevalence estimates. Methods This was a cohort study using deidentified, longitudinal, electronic health record data collected from 329 practices and 1 483 416 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 19 publications
2
40
1
Order By: Relevance
“…A total of 2,974,031 included patients had at least three clinical encounters in the previous two years. Details about this dataset can be found elsewhere [2,[14][15][16]. We used MedicineInsight data collected from 329 general practices between 1 January 2013 and 1 June 2016.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 2,974,031 included patients had at least three clinical encounters in the previous two years. Details about this dataset can be found elsewhere [2,[14][15][16]. We used MedicineInsight data collected from 329 general practices between 1 January 2013 and 1 June 2016.…”
Section: Methodsmentioning
confidence: 99%
“…This study had a large sample size, and patient characteristics within the MedicineInsight dataset are similar to the Australian population [2,14,16]. However, there are several limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As of July 2017, MedicineInsight had recruited 650 general practices with data pertaining to 3.6 million patients. [3,7,8] The Institutional Human Research Ethics Committee approved the study (H0015651). The study is reported as per the reporting of studies conducted using observational routinely collected health data statement for pharmacoepidemiology (RECORD-PE) guideline.…”
Section: Methodsmentioning
confidence: 99%